Instilling tolerance in early childhood at inclusive PAUD (a study at TK Talenta, Semarang City) - Ahimsa, Naila Irsyanda; Muthohar, Sofa (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2025)
Background : TK Talenta is an inclusive early childhood education institution currently serving 43 students, 28 of whom are children with special needs (CWSN) with various conditions. This presents challenges in instilling the value of tolerance from an early age. Aim : The purpose of this study is to provide insights into the process of instilling tolerance in an inclusive early childhood education setting, particularly focusing on how it is integrated into the learning process. Method : This study employed a qualitative case study method. Data were collected through observation, interviews, and documentation. The results revealed that the instillation of tolerance at TK Talenta was carried out through various activities, including habituation activities, learning activities, and non-learning activities. These activities demonstrated the integration of tolerance values in aspects such as peace, respect for individual differences, and awareness. Result : Observations showed that children demonstrated an understanding of tolerant behavior at each stage of school activities and were able to exhibit active participation and cooperation with one another. The implementation of tolerance values through three types of activities involving an inclusive environment served as a reinforcing medium for promoting tolerance within the school setting. Conclusion : The activities carried out at TK Talenta demonstrate that the instillation of tolerant attitudes can be effectively achieved through the integration of habituation, instructional, and non-instructional activities that are designed contextually and implemented continuously. All of these activities form an integral part of the learning process, which functions effectively and supports the implementation of inclusive education, while simultaneously instilling the values of tolerance from an early age.